Contribution of language to the creation of corporate social capital - Dhir, Krishna S. (Revista Internacional de Organizaciones, 2019)
With increased globalization of trade and business in a knowledge-based economy, and increasing diversification of the workforce, there is increasing pressure on multinational companies to report, and even measure, their social capital. This article explores the role of language in the creation of corporate social capital. The language used in a corporation is an asset, which creates value and corporate social capital in the use and exchange of ideas. Linguists have long attempted to assess the value of language as a commodity, but with little success. This article offers an approach to overcome this difficulty and to measure the value of language as an element of corporate social capital. To do so, it draws an analogy between the functions of language and functions of currency. The article goes on to suggest that multinational corporations should hold a portfolio of language skills, much as it does a portfolio of currencies.